Cluster headache is associated with an increased risk of depression: A nationwide population-based cohort study. (February 2013) - Liang, Jen-Feng; Chen, Yung-Tai; Fuh, Jong-Ling; Li, Szu-Yuan; Liu, Chia-Jen; Chen, Tzeng-Ji; Tang, Chao-Hsiun; Wang, Shuu-Jiun
Objective: To investigate whether cluster headache (CH) was a risk factor for depression in a nationwide population-based follow-up study. Background: There are few studies about the relationship between CH and depression, and prior research has been limited by cross-sectional studies or small sample sizes. Methods: We identified 673 CH patients from the Taiwan National Health Insurance database between 2005 and 2009. The two comparison cohorts included age-, sex- and Charlson's score-matched migraine patients ( n  = 2692) and controls (patients free from migraine or CH, n  = 2692). The cumulative incidence of depression was compared among these three cohorts until the end of 2009. We also calculated predictors of depression in the CH cohort. Results: After the median 2.5-year follow-up duration, the CH cohort had a greater risk for developing depression compared to the control cohort (adjusted hazard ratio; aHR = 5.6, 95% CI 3.0–10.6, p  < 0.001) but not the migraine cohort (aHR = 1.1, 95% CI 0.7–1.7, p  = 0.77). Of the CH patients, the number of cluster bout periods per year was a risk factor for depression (aHR = 3.8, 95% CI 2.6–5.4, p  < 0.001). Conclusion: Our results showed that CH is associated with an increased risk for depression. The strength of this association is similar to that of migraine.